Airborne Levels of Lung Carcinogens at an Ascon Manufacturing Site - Kyeongmin Lee; Sungwon Choi; Miyeon Kim; Dongwoo Song; Ki-Youn Kim (Aerosol and Air Quality Research)
Abstract We assessed the airborne concentrations of the dust (both total and respirable), quartz, polycyclic aromatic hydrocarbons, and elemental carbon in an ascon manufacturing environment to determine the exposure to operators and the likelihood of developing occupational respiratory disease. The Ascon production process is divided into four stages, namely, feeding, drying, mixing, and loading. During the feeding stage, the aggregate is transferred via hoppers to underground conveyors. The drying process removes moisture from the aggregate and maintains the required temperature for combining the aggregate, asphalt, and additives into ascon during the mixing stage. Finally, the ascon is disgorged from an outlet on the mixing machine and loaded onto dump trucks. The airborne concentrations of the total dust, respirable dust, and quartz measured at Hopper 1 and Hopper 6 were 8.540, 1.536, and 0.125 mg m−3, and 10.092, 3.989, and 0.331 mg m−3, respectively. The amounts of respirable dust and quartz by the vibrating screen totaled 12.362 and 1.645 mg m−3, respectively, and that of elemental carbon near a dryer burner equaled 0.001 mg m−3. The levels of the total dust, respirable dust, and quartz at the mixer outlet and in the dump truck zone were observed to be 0.685, 0.265, and 0.011 mg m−3, and 0.419, 0.036, and 0.011 mg m−3, respectively. Of the measured substances, only naphthalene was found at concentrations significantly lower than the permissible exposure limit (10 ppm), reaching only 0.274, 0.138, 0.192, and 0.237 ppm for the dryer burner, dump truck zone, dump truck waiting zone, and operational room, respectively. The conveyors on the ground, vibratory sieve, Bunker C oil tank, and mixer also exhibited very low concentrations of naphthalene—0.074, 0.088, 0.080, and 0.074 ppm, respectively. Relatively low levels of personal exposure to the total and the respirable dust (0.027 and 0.013 mg m−3) were measured during the operational tasks. However, operators were exposed to higher levels of respirable dust and quartz, 4.260 and 0.548 mg m−3, while cleaning the underground conveyors. Based our results, we conclude that whereas PAHs are emitted at very low concentrations during ascon production, quartz-containing aggregate dust is released in large quantities. This study presents the first environmental evaluation at an ascon production facility in terms of substances that cause lung cancer.